Validasi Pengembangan Modul Pembelajaran Ppkn Berbasis Mobile Untuk Meningkatkan Keterampilan Sosial Siswa Kelas XI SMA - Fella Farikhatus Sholikhah; Triana Rejekiningsih; Leo Agung Sutimin (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: The purpose of the research is to develop and validate the product in form a mobile-based module on Civics subjects. This study adopt the ADDIE model development design (Analysis, Design, Development, Implementation, and Evaluation). Validation and assessment from the validator, consist of: 1) validation from material experts obtained an average score of 3.72 qualified "Good"; 2) through media expert validation obtained an average score of 5.00 including the qualification "Very Good"; and 3) The total results obtained from the average score from the assessments of material experts and media experts related to the product being developed showed a result of 4.34 which entered the "Eligible" criteria for use in Civics learning in High Schools.Abstrak: Penelitian ini bertujuan untuk mengembangkan dan memvalidasi produk berupa modul berbasis mobile pada mata pelajaran PPKn. Penelitian ini menggunakan desain pengembangan model ADDIE (Analysis, Design, Development, Implementation, dan Evaluation). Validasi dan penilaian dari validator yaitu: 1) skor validasi dari ahli materi diperoleh rata-rata 3,72 dikualifikasikan “Baik”; 2) validasi dari ahli media dengan perolehan rata-rata skor 5,00 termasuk pada kualifikasi “Sangat Baik”; dan 3) Total perolehan hasil rata-rata skor dari penilaian ahli materi dan ahli media terkait produk yang dikembangakan menunjukkan hasil 4,34 yang masuk kriteria “Layak” untuk digunakan dalam pembelajaran PPKn di Sekolah Menengah Atas.